Cost‐effectiveness analysis of ledipasvir/sofosbuvir in patients with chronic hepatitis C: Treatment of patients with absence or mild fibrosis compared to patients with advanced fibrosis. Issue 9 (18th April 2017) - Buti, M.; Domínguez‐Hernández, R.; Oyagüez, I.; Casado, M. A.; Esteban, R.
Summary: To evaluate the cost‐effectiveness of ledipasvir/sofosbuvir (LDV/SOF) in treatment‐naïve patients with chronic hepatitis C (CHC) genotype 1 (GT1) in the absence or mild fibrosis (F0‐F1) versus advanced fibrosis (F2‐F4), from the perspective of the Spanish Health System. A Markov model was developed to simulate disease progression, estimating costs and outcomes [life years gained (LYG) and quality‐adjusted life years (QALY)] derived from starting with LDV/SOF in patients with F0‐F1 compared with F2‐F4. Therapy duration was 8 weeks in noncirrhotic patients with viral load <6 million IU/mL and 12 weeks in the remaining patients. Sustained virologic response rates were obtained from real‐world cohort studies. Transition probabilities, utilities and direct costs were obtained from the literature. A 3% annual discount rate was applied to costs and outcomes. Sensitivity analyses were performed. LDV/SOF in F0‐F1 patients was a dominant strategy, being more effective (19.85 LYG and 19.80 QALY) than beginning treatment in F2‐F4 patients (18.63 LYG and 16.25 QALY), generating savings of €9228 per patient (€3661 due to disease management and monitoring). In a cohort of 1000 patients, LDV/SOF in F0‐F1 patients decreased the number of cases of decompensated cirrhosis (93%), hepatocellular carcinoma (97%) and liver‐related deaths (95%) and prevented 6 liver transplants compared to initiating LDV/SOF in F2‐F4 patients. In CHC treatment‐naïve GT1 patients, starting treatment with LDV/SOF in patients with F0‐F1 compared to those with F2‐F4 increases effectiveness by 1.22 LYG and 3.55 QALY gained and reduces disease burden and it is associated with cost savings.